The Role of Free Cash Flow in Improving Earning Management - Yusrawati; Pratami, Yolanda; Lova, Oke Adinda; Valdi, Fitra (GoAcademica Research & Publishing, 2024)
The objectives of this study revolve around examining the influence of free cash flow, financial distress, employee differentiation, and corporate social responsibility on profit management within transport companies that are publicly listed on the Indonesian Stock Exchange during the period spanning from 2019 to 2021. To select samples, specialized sampling techniques were employed in this research. A total of 32 companies were chosen as representatives for the study. Duplicate regression analysis, facilitated by SPSS version 23.0, served as the primary analytical tool. The findings of this study indicate that free cash flows have a significant impact on income control. However, it was observed that income management remains unaffected by financial issues, employee turnover, or corporate social responsibility.